SISTEM REPOSITORY PERPUSTAKAAN PADA UNIVERSITAS BANTEN JAYA BERBASIS WEB (STUDI KASUS : UNIVERSITAS BANTEN JAYA) - R Kania; Rustam Effendi; Muh. Rizal Sidik (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
The library repository system located at Banten Jaya University is not currently utilizing information technology to the maximum. This is seen from the library member registration information system and the ongoing report data storage system, the system is still manually done by filling out the form on paper and also still the manual storage of scientific work report data, if it has finished filling out the form the library must re-input on the application. In this way it is certainly less effective and efficient. Based on the results of the system research that the authors conducted, with the update of the repository system this web-based library can provide ease to the officer in managing the library information system. The research method used is waterfall development model, which consists of analysis, design, implementation, and testing. The development of this web-based library information system uses php7 language for system functionality because it is very effective for building web-based applications. The result of this study is the development of repository applications that can facilitate students in accessing scientific work in the Library of Banten Jaya University. Using the Repository application can reduce damage, lose scientific work collections, make it easier to use libraries and save space usage and by implementing repository applications are expected to support library performance and assist library users in finding the information they need.